Krishna
0

Step 1: Find the required term from the given rule.

            NOTE: Substitute the suitable n value in the given rule to find the term

          

            EXAMPLE: To find the a_3 term, replace n with the 2

                               a_{n+1} = 4a_n - 7

                         a_{2+1} = 4a_2 - 7 (since a_2=4k-7)

                         a_3 = 4(4k - 7) - 7

Step 2: Equate the term with the given value and simplify for the k value  

            EXAMPLE: 4(4k-7) = 13

                                16k − 35 = 13